2013
DOI: 10.1086/669083
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and Device-Specific Risk Factors for Peripherally Inserted Central Venous Catheter—Related Bloodstream Infections

Abstract: We identified several novel factors related to PICC BSIs. These factors may inform preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 35 publications
2
45
0
1
Order By: Relevance
“…The number of lumen was found to play a part in the incidence of PICCrelated infections. Indeed, Chopra et al found that double and triple lumens were associated with greater risk of infection than single lumen ones (Hazard ratios: 4.08 (p = 0.006) and 8.52 (p = 0.0003) for double and triple lumen PICCs, respectively) [7], corroborating what Pongruangporn et al showed one year before (OR for double lumen, 1.89; p = 0.01; OR for triple lumen, 2.87; p = 0.004) [22]. The large majority of the PICCs we placed in our patients were single lumen (80.6 %), this is probably why the number of lumen did not turn out to be a significant risk factor of infection in our statistical analysis.…”
Section: Microbiologysupporting
confidence: 76%
“…The number of lumen was found to play a part in the incidence of PICCrelated infections. Indeed, Chopra et al found that double and triple lumens were associated with greater risk of infection than single lumen ones (Hazard ratios: 4.08 (p = 0.006) and 8.52 (p = 0.0003) for double and triple lumen PICCs, respectively) [7], corroborating what Pongruangporn et al showed one year before (OR for double lumen, 1.89; p = 0.01; OR for triple lumen, 2.87; p = 0.004) [22]. The large majority of the PICCs we placed in our patients were single lumen (80.6 %), this is probably why the number of lumen did not turn out to be a significant risk factor of infection in our statistical analysis.…”
Section: Microbiologysupporting
confidence: 76%
“…Contemporary data on risk factors have limitations in terms of generalizability. [5][6][7]9 We found independent predictors of CLABSI included duration of CVC presence and more frequent CVC access-specifically, higher number of lab tests drawn. Although we found an association between number of intravenous medications given and CLABSI in bivariate analysis, this association was not seen in our multivariate analysis, possibly owing to limited power.…”
Section: Resultsmentioning
confidence: 75%
“…Üçüncü basamak bir sağlık kuruluşundan yapılan çalışmada, YBÜ'de çift lümenli kateter kullanımının SKİ-KDE riskini 1,89, üç lümenli kateterlerin ise 2,87 kat arttırdığı bildirilmiştir [31] . Evde parenteral bakım alan çocuklarda SKİ-KDE riskinin değerlendirildiği diğer bir çalışmada ise, birden çok lümenli kateterde enfeksiyon riskinin arttığı istatistiksel olarak anlamlı bulunmuştur [32] .…”
Section: Santral Kateter İlişkili Kan Dolaşımı Enfeksiyonu öNleme Demetiunclassified